The role of LMX and organizational climate in improving performance and effectiveness of local public administration: evidence from the Metropolis GZM - Marzec, Izabela (Rozwój Regionalny i Polityka Regionalna, 2023)
Since the 1990s, along with the transformation of public administration and the emergence of new concepts of public management, the improvement of organisational effectiveness and performance (OEP) of local public administration has become an important goal of regional policies in many countries. The OEP of local public administration has started to be considered as an essential factor affecting the process of regional socio-economic development. However, to improve the performance of local public administration, factors influencing the OEP of public administration organizations need to be determined. Consequently, the purpose of this paper is to identify how such factors as the quality of relations between leaders and subordinates as well as learning climate influence the OEP of public administration organizations. Method/approach: The paper presents the results of a survey research conducted among 153 employees of municipal offices in the Górnośląsko-Zagłębiowska Metropolis (i.e. Metropolis GZM). A model of relationships between LMX, organizational learning climate, and the OEP was examined with the use of Structural Equation Modeling and path analysis. Findings: It was found that the LMX affected the OEP only indirectly through its impact on organizational learning climate which in turn influences the OEP. Therefore, the study also revealed that organizational learning climate mediated the relationship between the LMX and the OEP. Originality: The presented results of the study have provided empirical evidence regarding the influence of LMX and organizational climate on the OEP of public organizations which was hitherto absent in the literature on the subject. A novel conclusion from this study is that the high quality of relationships between leaders and subordinates and organizational learning climate improve the OEP of local public administration organizations. Highly effective local public administration can become a driver of the regional development promoting new ideas, innovation and local incentives.